PELESTARIAN TANAMAN PANGAN DENGAN TEKNIK KULTUR IN VITRO - Widyastuti, Netty (Jurnal Teknologi Lingkungan, 2000)
Saving the world genetic germplasm has been world community’s concern. It is a must to find a way to preserve Indonesian’s food plant biodiversity. In vitro technique culture is a proper alternative conservation of food plants. The technique is suitable for short viable seeds and vegetative multiplicating plants. Based on storage length, in vitro technique can be divided into two catagories. First short or medium term storage which intends to suppress the growth of the seed temporarily and secondly long term storage proposes to halt metabolic activity, however, the cells are still viable. There are some advantages of in vitro preservation such as savingdistinctive plants, foliage, plant without seeds, free pathogens, free disruption of environments. It is preserved free pathogen, and working on relative small room enough.